2009
DOI: 10.1007/s10071-009-0300-6
|View full text |Cite
|
Sign up to set email alerts
|

Domesticated dogs’ (Canis familiaris) use of the solidity principle

Abstract: Organisms must often make predictions about the trajectories of moving objects. However, often these objects become hidden. To later locate such objects, the organism must maintain a representation of the object in memory and generate an expectation about where it will later appear. We explored adult dogs' knowledge and use of the solidity principle (that one solid object cannot pass through another solid object) by evaluating search behavior. Subjects watched as a treat rolled down an inclined tube into a box… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 59 publications
2
25
1
Order By: Relevance
“…In seminal experiments (Baillargeon, 1995;Baillargeon, Spelke, & Wasserman, 1985), it was shown that threeand-a-half-month-old infants form representations of hidden objects and make the inference that a solid object cannot move through the space occupied by another solid object. Evidence has since been collected that nonhuman animals also represent physical objects and reason about the motion of physical objects in accordance with the basic constraint of solidity of material bodies (Call, 2007;Kundey, De Los Reyes, Taglang, Baruch, & German, 2009;Pattison, Miller, Rayburn-Reeves, & Zentall, 2010). Nevertheless, the fact that human infants exhibit evidence for object permanence and inference about the physical properties of objects starting from three and a half months of age is compatible with both a nativist and an empiricist view, the former arguing for maturation and the latter for learning.…”
Section: Natural-born Physicistsmentioning
confidence: 74%
“…In seminal experiments (Baillargeon, 1995;Baillargeon, Spelke, & Wasserman, 1985), it was shown that threeand-a-half-month-old infants form representations of hidden objects and make the inference that a solid object cannot move through the space occupied by another solid object. Evidence has since been collected that nonhuman animals also represent physical objects and reason about the motion of physical objects in accordance with the basic constraint of solidity of material bodies (Call, 2007;Kundey, De Los Reyes, Taglang, Baruch, & German, 2009;Pattison, Miller, Rayburn-Reeves, & Zentall, 2010). Nevertheless, the fact that human infants exhibit evidence for object permanence and inference about the physical properties of objects starting from three and a half months of age is compatible with both a nativist and an empiricist view, the former arguing for maturation and the latter for learning.…”
Section: Natural-born Physicistsmentioning
confidence: 74%
“…The A-not-B task required object permanence, as the dogs had to realize that once food disappeared into the bucket, it had not disappeared from the room. The cylinder task necessitated an understanding of physical properties, such as the solidity principle (Kundey et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…This "core knowledge" is often conceived of as the product of evolutionary pressures for organisms to solve domain-specific problems, with the solutions conserved over ontogeny and phylogeny (Spelke & Kinzler, 2007 for review). Core knowledge has been documented in a variety of species (e.g., Agrillo, Dadda, Serena, & Bisazza, 2008;Cantlon & Brannon, 2006;Kundey, De Los Reyes, Taglang, Baruch, & German, 2010;Regolin & Vallortigara, 1995;Santos, 2004;Spelke & Lee, 2012) and across diverse human cultures (Dehaene, Izard, Pica, & Spelke, 2006;Gordon, 2004;Pica, Lemer, Izard, & Dehaene, 2004), and in some cases has been shown to be present, in both humans and non-human animals, at birth (Izard, Sann, Spelke, & Streri, 2009;Regolin & Vallortigara, 1995). Finally, because it can emerge under controlled rearing conditions in which animals' opportunities for learning are drastically reduced, core knowledge is often proposed to be independent of specific learning experience (e.g., .…”
Section: Core Knowledge In Early Cognitionmentioning
confidence: 99%